OSCE : Equipment - Kundan Mittal; Prashant Kumar; H K Aggarwal (Wolters Kluwer Medknow Publications, 2019)
Provision of respiratory support by positive pressure ventilation is one of important function of intensive care units. Mechanical ventilation is used to replace or supplement the work carried out by respiratory system. Mechanical ventilation is a supportive intervention rather therapeutic and is full of hazards.